The Ideology of the European Union - IUKOV, Evgeny A.; ZHELTOV, Viktor V. (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
The paper deals with the process of the European integration, which led to the emergence of the EU. It defines and analyzes the key ideological elements both at the national and at the international levels, which form the EU ideology. The authors have considered and analyzed the main publications on this subject, and have kept the track of the evolution of the EU ideology from the United States of Europe to the instrument of overcoming the national conflicts. The authors have underlined such key aspects of the EU ideology as freedom, equality, respect to the human rights, multiculturalism, and the ideology of openness. They have also revealed the following reasons for the crisis of the European ideology: economic inequality between the EU members, the increase in the extremists’ right-wing forces, and the process of self-determination of Catalonia and Scotland, and counter-productive sanctions towards Russia. The authors have concluded that initially the EU was being built on the idea of the economy as a means of peace-keeping between the peoples of Europe and their consolidation, while the ideological component was supplemented later and attracted controversy among the citizens and members of the Union. The authors have also suggested the methods for overcoming the crisis of the EU ideological structure.